Case report: Clinical management of recurrent small cell lung cancer transformation complicated with lung cancer-induced acute pancreatitis after lung adenocarcinoma surgery - Zhang, Suyun; Guo, Ningjing; Zhang, Qianyuan; Wang, Yao; Yang, Sheng; Chen, Xiangqi (Frontiers in Pharmacology, 2023)
In the diagnosis and treatment of non-small cell lung cancer (NSCLC), the histological type may change from lung adenocarcinoma to lung squamous cell cancer or small cell lung cancer (SCLC). Pancreatic metastasis is extremely rare in advanced lung cancer, and pancreatitis characterized by lung cancer metastasis-induced acute pancreatitis (MIAP) is more rare. This paper reports in detail the clinical diagnosis and treatment of a female patient with lung adenocarcinoma who relapsed after radical surgery and progressed after multiple treatments. A second pathological biopsy revealed SCLC transformation, and the patient developed pancreatic metastasis and lung 2 cancer MIAP during follow-up treatment. This paper mainly suggests that clinicians should pay attention to the possibility of pathological type transformation in the progression of advanced NSCLC, closely observe the dynamic changes of tumor markers and pay attention to the re-biopsy pathological analysis. In addition, it provides clinical experience and scientific reference for the discovery, diagnosis and treatment of transforming SCLC and lung cancer MIAP.